Queens of academe beauty pageants and campus life - Tice, Karen Whitney, 1955- (New York ; Oxford : Oxford University Press, 2012)
Higher education is an unlikely venue for showcasing ideals of femininity, yet campus beauty pageants have increased in popularity in a cultural marketplace conjoining personal empowerment with beauty and style. Tice examines the desires and racial and political agendas that propel students onto collegiate catwalks.
Description based on online resource; title from PDF title page (viewed on Apr. 26, 2012).
Includes bibliographical references and index.
Keywords: Women college students -- United States; Beauty contestants -- United States; Beauty contests -- United States; Universities and colleges -- United States -- Sociological aspects